The Limits to Competition in Urban Bus Services in Developing Countries - Estache, Antonio; Gómez-Lobo, Andrés (World Bank, Washington, D.C., 2013)
The authors make the case for the return of regulation in the organization of urban bus services in developing countries. During the past three decades urban public transport policy has gone through several phases. The 1980s and 1990s were characterized by liberalization of the sector from public ownership and monopoly provision. The experience of several countries, in particular Chile, indicates that a full liberalization of the sector may not be the welfare-maximizing option. The authors discuss the market failures that justify this claim and present the regulatory options available in this emerging new role of government. Throughout the paper they illustrate ideas with examples from Chile, Colombia, and a few other countries.